Metastasizing uterine mullerian adenosarcoma in a young female: Diagnostic enigma - Rashmi Patnayak; Nandyala Rukmangadha; Pabbu Architha; Gajjala Sivanath Reddy; Amarchala Yadagiri Lakshmi; Thiruvengadaswamy Kannan; Amitabh Jena (Wolters Kluwer Medknow Publications, 2018)
Uterine adenosarcomas are uncommon tumors. It is a biphasic tumor with both epithelial and mesenchymal component. The epithelial component is benign in nature, and the mesenchymal component is malignant. Metastasis is rare in adenosarcoma. We report a case of adenosarcoma with lymph nodal metastasis. A 20-year-old female presented with history of per vaginal bleeding for 1 month. Per vaginal examination revealed a fungating mass protruding through the cervical os. Ultrasonography and magnetic resonance imaging showed a large intrauterine mass. Biopsy of the mass done at an outside hospital was reported as rhabdomyosarcoma. Hence, she was given one cycle of neoadjuvant chemotherapy. Following this, she had profuse bleeding. Emergency hysterectomy with pelvic lymph nodal dissection was performed. The final histopathology was reported as adenosarcoma. One pelvic lymph node showed metastatic deposit of rhabdomyosarcomatous element. In young females presenting with polypoidal mass, uterine adenosarcoma can be considered in the differential diagnosis.